Conventional laparotomy for management of caesarean scar ectopic pregnancy: a case report - Mhaske, Nilesh C.; Jhaveri, Rujul; Prasad, Madhva; Kharat, Deepali; Fonseca, Michelle N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Increase in the rates of caesarean deliveries has led to a concurrent rise in the number of caesarean scar ectopic pregnancies (CSEP). With recent advances, diagnosis can be made at an early gestational age, hence facilitating a prompt intervention. With the varied treatment options available, choosing the right one may possess a clinical dilemma. However, in a low resource setting, conventional laparotomy may be the only option feasible. A case of CSEP managed with laparotomy is presented.